2010
DOI: 10.1109/tbcas.2010.2081364
|View full text |Cite
|
Sign up to set email alerts
|

A Miniature-Implantable RF-Wireless Active Glaucoma Intraocular Pressure Monitor

Abstract: Glaucoma is a detrimental disease that causes blindness in millions of people worldwide. There are numerous treatments to slow the condition but none are totally effective and all have significant side effects. Currently, a continuous monitoring device is not available, but its development may open up new avenues for treatment. This work focuses on the design and fabrication of an active glaucoma intraocular pressure (IOP) monitor that is fully wireless and implantable. Major benefits of an active IOP monitori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(56 citation statements)
references
References 25 publications
0
55
0
1
Order By: Relevance
“…Such measurements can only be obtained for up to 24 h because of side complications that accompany long-term use [41][42][43] . To overcome the aforementioned limitations, implants based on radio-frequency (RF) technologies have been used to monitor endovascular pressure 44 , intracranial pressure (ICP) 45,46 , and IOP [47][48][49][50][51][52][53][54][55][56][57][58] . The typical size of these implants ranges from a millimeter to a few centimetres.…”
Section: Introductionmentioning
confidence: 99%
“…Such measurements can only be obtained for up to 24 h because of side complications that accompany long-term use [41][42][43] . To overcome the aforementioned limitations, implants based on radio-frequency (RF) technologies have been used to monitor endovascular pressure 44 , intracranial pressure (ICP) 45,46 , and IOP [47][48][49][50][51][52][53][54][55][56][57][58] . The typical size of these implants ranges from a millimeter to a few centimetres.…”
Section: Introductionmentioning
confidence: 99%
“…This design approach is in contrast to the modularity that has characterized embedded system design and enabled it to address a highly diverse application space. The miniature sensor node application space is similarly diverse, ranging from implantable medical monitors [4][5][6] to nearly invisible surveillance [7]. Hence, a modular design approach that enables extensive reuse of chip modules is a key to fully address its application space.…”
Section: Introductionmentioning
confidence: 99%
“…Some of the wireless implantable systems that have recently been developed include wireless systems to record neural activity [2], continuously monitor blood glucose levels [5], monitor cardiovascular pressure [6], and monitor intraocular pressure [7]. The first two systems both make use of inductive coupling for power transfer and data communications while the latter two systems use RF energy for powering and data transfer.…”
Section: General Discussion Of Wireless Implantable Technologymentioning
confidence: 99%
“…They were not able to develop a fully integrated system that is able to provide enough power for the rest of the circuit to operate. Chow et al also developed an implantable system for measuring intraocular pressure [7] as shown in Figure 8 mm of pork tissue, but were only able to achieve an operating range of 1.5 cm. A block diagram of the implant is shown in Figure 9.…”
Section: Far Field Devicesmentioning
confidence: 99%
See 1 more Smart Citation